Loss of horizontal macular ganglion cell complex asymmetry: an optical coherence tomography indicator of chiasmal compression. Issue 1 (24th October 2018) - Jørstad, Øystein Kalsnes; Wigers, Andreas Reidar; Marthinsen, Pål Bache; Moe, Morten Carstens; Evang, Johan Arild
Abstract : Objective: To estimate the macular ganglion cell complex (GCC) asymmetry in patients with suprasellar tumours, to compare its diagnostic performance to the nasal GCC thickness and visual field (VF) and to investigate how the parameters correlate with magnetic resonance imaging (MRI) findings. Methods and analysis: Cross-sectional study of patients with suprasellar tumours affecting the optic chiasm. Macular optical coherence tomography (OCT) scans were evaluated for nasal GCC sector thinning and loss of normal GCC asymmetry between corresponding nasal-temporal sectors. Equivalently, VFs were analysed for defects compatible with chiasm dysfunction. The relationship between optic chiasm and tumour was measured on MRI. Results: Thirty-three eyes of 33 patients were included. There were OCT findings in 14 eyes. Nasal GCC thinning was found in 9 eyes and loss of GCC asymmetry in 12 eyes; the two parameters were not significantly different with respect to number of positive findings (p=0.45). Loss of GCC asymmetry, however, occurred in 5 eyes among 24 without GCC thinning (proportion 0.21; 95% confidence interval 0.071 to 0.42). In 8 eyes, VF indicated pathology; of these, 7 had concurring OCT findings. The prevalence of OCT and VF findings increased significantly with suprasellar tumour extension on MRI. Conclusion: The diagnostic capabilities of nasal GCC thinning and loss of GCC asymmetry were comparable, whilst their complementary performances increased the proportion of eyes in which OCT suggested compression. The prevalence of both OCT and VF findings grew with suprasellar tumour extension. In several cases, however, structural findings on OCT preceded detectable VF deficits.